Pendidikan Karakter Berbasis Cinta Damai di SD/MI - Subiyono, Subiono; Mulyani, Ani Sri; Nurishlah, Laesti; Damayanti, Gita (Peneliti.net, 2021)
Character education is not only about conveying values, but also about helping students understand and internalize those values through active learning, such as discussions, simulations, and value-based projects. This study aims to elaborate peace-based character education which is associated with its impact on student character building in elementary / MI. The results show, peace-loving character education helps create a safe, inclusive, and conducive learning environment for student growth and development. This has an impact on increasing learning motivation, active participation in school activities, and increasing academic achievement. The implementation of peace-loving character education has the potential to reduce the incidence of conflict, fighting, and violence in the school environment. Students become more skilled in managing conflict constructively and peacefully, creating a more harmonious atmosphere.